BrainDen.com - Brain Teasers
• 0

## Question

Does the weight of an elephant equal the weight of the mosquito?

Let x be the weight of the elephant, y be the weight of the mosquito. Call the sum of the two weights 2v, then x+y=2v

From this equation we can obtain two more:

x - 2v = -y

and

x = -y + 2v

multiply:

x^2 - 2vx = y^2 - 2vy

x^2 - 2vx + v^2 = y^2 - 2vy + v^2

OR

(x-v)^2 = (y-v)^2

take square roots:

(x-v) = (y-v)

x = y

The elephant's weight equals the mosquitoes.

What is wrong here?

## Recommended Posts

• 0 when you take the square root you ignore an answer to the problem

##### Share on other sites
• 0 (x-v)^2 = (y-v)^2

take square roots:

(x-v) = (y-v)

Mathematically when you take the square root of both sides you need a plus or minus on at leat one side:

(x-v) = ±(y-v)

The minus route gives you x + y = 2v again. Obviously you should choose to use the minus out of the plus or minus because anyone would assume they cannot be the same mass, yet you get back to your original equation and realize you are just wasting your time like I just realized.

##### Share on other sites
• 0

good job! that problem can get confusing.

## Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account. ×   Pasted as rich text.   Paste as plain text instead

Only 75 emoji are allowed.

×   Your previous content has been restored.   Clear editor

×   You cannot paste images directly. Upload or insert images from URL.

×